Implementasi Kebijakan Program Beras Miskin (Raskin) di Desa Kejapanan Kecamatan Gempol Kabupaten Pasuruan - Januarti, Stella Erdityaningrum; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2014)
The purposes of this research was analyzing and describing about implementation of the rice for poor program in Kejapanan Village Gempol Subdistrict Pasuruan Regency as well as was identifing the obstacles of this program. This research used descriptive qualitative method. Collecting of data used observation, interview and documentation. Data analizing technique used descriptive qualitative. The results showed that as long as the implementation of rice program didn’t any evaluation from the citizen or subdistrict. It happened because the government Kejapanan village didn’t had an available legally action system for the villagers. On the other hand, monev team never checked the rice program and the officers of this program never did observation about it.